1983
DOI: 10.1111/j.1748-1716.1983.tb07185.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of different fibre types in human skeletal muscles 2. A study of cross‐sections of whole m. vastus lateralis

Abstract: In order to determine the total number of fibres and the extent to which the relative occurrence of different fibre types varies within m. vastus lateralis, 15 micrometers thick cross-sections of whole muscles were prepared. The total number of type 1 and type 2 fibres was determined in every 48th square millimetre of the section, and the results thus obtained were analysed using a computer program allowing an assessment of bivariate data in the form of contour plots. The total number of fibres varied both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
1
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(155 citation statements)
references
References 25 publications
(25 reference statements)
6
144
1
4
Order By: Relevance
“…In addition, if motor axons are in a refractory state at the instant of stimulus application, this can suppress superimposed torque, particularly at higher values of MVT. 32 Furthermore, there is a nonrandom distribution of fiber types in the quadriceps, with relatively more type II fibers 33 and more larger motor units 34,35 in superficial layers. Percutaneous stimulation, with lower stimulation currents will not reach deep into the muscle tissue, 18 and, therefore, potentially more type II fibers may be activated with submaximal muscle compared with maximal nerve stimulation.…”
Section: Discussion Superimposed Torquementioning
confidence: 99%
“…In addition, if motor axons are in a refractory state at the instant of stimulus application, this can suppress superimposed torque, particularly at higher values of MVT. 32 Furthermore, there is a nonrandom distribution of fiber types in the quadriceps, with relatively more type II fibers 33 and more larger motor units 34,35 in superficial layers. Percutaneous stimulation, with lower stimulation currents will not reach deep into the muscle tissue, 18 and, therefore, potentially more type II fibers may be activated with submaximal muscle compared with maximal nerve stimulation.…”
Section: Discussion Superimposed Torquementioning
confidence: 99%
“…This strongly suggests that the child/adult differences in Figure 1 are likely to be a very real phenomenon that extends to a range of skeletal muscles in humans. Lexell and his co-workers 33 have reported that the distribution of different ®bre types varies within a muscle, mainly as a function of depth, with a predominance of Type 2 ®bres at the surface and Type 1 ®bres in deeper regions of the muscle. Thus, the ®bre type distribution is not random and while every endeavour was taken during the collection of muscle biopsy samples to ensure consistency, this must be taken into consideration when data on ®bre type composition are compared with functional variables.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the vastus lateralis a slight predominance of slow twitch fibres has been shown in the deeper regions of the muscle tissue (Lexell et al 1983). Therefore a greater penetrative depth of near-infrared light would likely favour faster microvascular oxygen pressure (McDonough et al 2004) and thus [HHb] kinetics (Ferreira et al 2005) during recovery and may explain some of the differences between groups.…”
Section: [Hhb] Kineticsmentioning
confidence: 99%